Flexural Performance of Composite Ultra-High-Performance Concrete-Encased Steel Hollow Beams - Tu'ma, Nasser Hakeem; Aziz, Mustafa Raad (Civil Engineering Journal, 2019)
Composite members have been widely used in the construction of medium- and high-rise buildings. The results of the development of a new structural member by experimental investigation of the flexural behavior of hollow composite beams are presented in this paper. This research aims to exploit the properties of composite sections and their strength in developing a new approach for overcoming the problems of service pipes in buildings. A hollow steel section encased fully in concrete is used to form a composite hollow beam. The structural benefit provided by the steel section (composite part) is adopted to increase the stiffness of the member. The hollow part is employed to provide services and economic benefits by reducing the amount of expensive ultra-high-performance concrete (UHPC) used and decreasing the self-weight of the member. The flexural strength of 11 UHPC beams is tested under two-point loads. The variables in this investigation include the type of hollow core mold material and the size, location, and shape of steel hollow sections in the middle and tension zones of the cross-section. Experimental results are compared and discussed. The tested results show that the flexural capacity and stiffness of the UHPC-encased steel hollow beams are 109% and 23.5% higher than those solid beams, respectively.